GPX4 regulates cellular necrosis and host resistance in mycobacterium tuberculosis infection - Amaral, Eduardo P. (2022)
Intramural Research Program of NIAID/NIH. Wellcome. Medical Research Council (UK). Intramural Research Program of the Oswaldo Cruz Foundation and of the Jose Silveira Foundation. Conselho Nacional de Desenvolvimento Cient´ıfico e Tecnológico (CNPq).